THE EFFECT OF RETURN ON ASSETS AND THE CURRENT RATIO ON STOCK RETURN IN TECHNOLOGY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Riani, Ayundah; Zulkifli; Mohamad Trio Febriyantoro; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto; Budi (Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine and analyze the effect of return on assets (ROA) and current ratio (CR) on stock returns in technology companies listed on the Indonesia Stock Exchange for the 2019–2021 period. The population of this study amounted to 26 companies. The sampling technique using the purposive sampling method obtained data from 6 companies. The results of this study indicate that ROA has a positive and significant effect on stock returns, while CR has no significant effect on stock returns.